From apparent attenuation towards physics-based source terms – a perspective on spectral wave modeling in ice-covered seas - Herman, Agnieszka (Frontiers in Marine Science, 2024)
Numerical modeling of waves in sea ice covered regions of the oceans is important for many applications, from short-term forecasting and ship route planning up to climate modeling. In spite of a substantial progress in wave-in-ice research that took place in recent years, spectral wave models – the main tool for wave modeling at regional and larger scales – still don’t capture the underlying physics and have rather poor predictive skills. This article discusses recent developments in wave observations and spectral wave modeling in sea ice, identifies problems and shortcomings of the approaches used so far, and sketches future directions that, in the opinion of the author, have the potential to improve the performance of wave-in-ice models.